The Antecedents and Consequences of Using Online Learning in Elementary School During a Pandemic: A Systematic Literature Review - Atikah Syamsi; Patimah Patimah; Heru Mudiyanto (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThis study aims to trace and examine the antecedent perspectives and the consequences of online learning portraits in elementary schools during the pandemic by reviewing research articles published in reputable journals. Due to educators' efforts to reduce learning loss, it is hoped that it will be able to become an analytical force concerning driving causes and influencing factors. This research used a systematic literature review approach which uses published resources in the form of books, journals, and other scientific works. Analytical techniques are carried out through descriptive analysis techniques from online literature searches. In addition to using traceability, researchers also use biometric techniques with the VosViewer Visualization application. The goal is to biometrically map variables that are closely related to antecedents and consequences. After searching on Google Scholar, Ebsco, and Crossref using the keywords â€œOnline Learningâ€ AND â€œPandemic Covidâ€ AND â€œLearning Loss, researchers found 100 reputable journal articles (indexed by Scopus) that were relevant to the keyword. Of the 100 journal articles found, 22 journal articles were screened, while 22 journal articles were excluded because there were no full-text articles. As a result of the feasibility or compatibility examination of 78 full-text journals, 68 articles were found to be unfit due to duplications and/or failure to match the criteria, leaving 10 full-text journal articles that could be examined. The result obtained from the data analysis is that the factors of using online learning are the replacement of learning spaces in the classroom becoming classless and limitless. Besides that, the readiness in adapting online learning is also an important part of the expected changes because teachers are expected to also be able to accompany students in online learning. However, what is still found in some articles is the speed and ability of the school internet network which is also a driver for optimizing the use of online learning. The consequence is that emergency online learning during the Covid-19 Pandemic makes teachers have to practice special skills in adapting to technological developments, so teachers at the elementary level also need special training, either in program preparation or in continuous professional development, to create online course content that can be used by all students.Keywords: online learning, learning loss, elementary school, antecedents, consequences.AbstrakPenelitian ini bertujuan untuk menelusuri dan mengkaji dari perspektif anteseden dan konsekuensi potret pembelajaran online di Sekolah Dasar/Madrasah Ibtidaiyah (SD/MI) selama pandemi dengan strategi penelusuran terhadap artikel penelitian yang dipublikasikan dalam jurnal bereputasi. Sehingga diharapkan mampu menjadi daya analisa terkait faktor pendorong (anteseden) dan faktor pengaruh sebagai konsekuensi dari upaya pendidik dalam meminimalisir learning loss. Metode penelitian ini menggunakan pendekatan Sistematik Literatur Reviu dengan menggunakan kajian terhadap sumber, baik berupa buku ataupun jurnal serta karya ilmiah lainnya. Teknik analisis yang dilakukan melalui teknik analisa deskriptif dari penelusuran literatur secara online menggunakan traceability dan juga menggunakan teknik biometrik dengan aplikasi VosViewer Visualization. Tujuannya adalah untuk memetakan secara biometrik variabel yang terkait erat dengan anteseden dan konsekuensi. Adapun hasilnya berdasarkan hasil pencarian di Google Schoolar, Ebsco dan Crossref menggunakan kata kunci â€œOnline Learningâ€ AND â€œPandemic Covidâ€ AND â€œLearning Loss, peneliti mendapatkan 100 artikel jurnal bereputasi (terindeks scopus) yang relevan dengan kata kunci. Dari 100 artikel jurnal yang ditemukan selanjutnya dilakukan screening, sedangkan 22 artikel jurnal dilakukan eksklusi karena tidak terdapat artikel full text. Dari hasil penilaian kelayakan atau kecocokan terhadap 78 jurnal full text, ada 68 artikel yang dinyatakan tidak layak karena ada duplikasi dan juga tidak sesuai dengan kriteria, sehingga diperoleh 10 artikel jurnal full text yang selanjutnya dapat direview. Hasilnya diperoleh anteseden (pendorong) pemanfaatan pembelajaran online yaitu adanya pengganti ruang belajar dalam kelas menjadi tanpa kelas dan tanpa batas, selain itu faktor kesiapan dalam melakukan adaptasi juga menjadi bagian penting dari perubahan yang diharapkan, karena guru sebagai pendamping siswa diharapkan juga mampu mendampingi siswa dalam pembelajaran online. Namun yang masih banyak ditemukan dalam sejumlah artikel ialah kecepatan dan kemampuan jaringan internet sekolah yang juga menjadi pendorong adanya optimalisasi pemanfaatan belajar online ini. Adapun konsekuensinya ialah pembelajaran online darurat selama pandemic Covid-19 membuat guru harus berlatih keterampilan khusus dalam melakukan adaptasi dengan perkembangan teknologi. Sehingga guru di tingkat SD/MI juga membutuhkan pelatihan khusus, baik dalam persiapan program atau dalam pengembangan profesional keberkelanjutan untuk menciptakan konten kursus online yang dapat digunakan oleh semua siswa.Kata kunci: online learning, learning loss, elementary school, antecedents, consequences.